A study on the law and the practical aspects of law enforcement on massage parlour activities / Shareen Fiza Arshad, Sitie Mat Yusuf and Wan Mohd I'zzat Wan Abdullah - Arshad, Shareen Fiza; Mat Yusuf, Sitie; Wan Abdullah, Wan Mohd I'zzat (2008)
This project paper focus on the law and actual practice of local council, in issuance of license and to monitor activities of massage parlour in Selangor especially in Subang Jaya locality. Here, it concentrates on the rules and regulations which fall under Beauty and Health Care Centre ( Subang Jaya Municipal Council) By-Laws 2007. It is submitted that there is still ambiguity in certain area that can be improvised. On another hand, this project paper can also provide suggestion on the improvement to be made on by-law particularly with regards to the interpretation position related to massage parlour. Another main issue that is discussed is the inadequacy in law enforcement. It is submitted that, based on the problems normally faced by these law enforcers for example lack of manpower, we had identified several recommendations that may be considered to overcome the problem. It is submitted that the law can still be improved to increase its effectiveness. One way to do it is by increasing the co-ordination between local council and police force also still can be improved. This will eventually improve on the enforcement system and recording system. Through proper co-ordination, more organized operation can be made and eventually a proper record and statistic system can be established.